Application of Potassium Nitrate Influenced Yield, Nutrient and Water Use Efficiency and Profitability of Gossypium herbaceum in Canal Irrigated Region of Western India - Sharma, Babloo; Singh, Bhupender; Kumari, Pratibha; Kumari, Reena; Sharma, Charu; Galav, Atul; Chaturvedi, Deepak (International Journal of Economic Plants, 2025)
The study was carried during April to October, 2022 in Srigangangar district of Rajasthan, India, at randomly selected farmer's field with two treatments to validate the efficiency of potassum nitrate in cotton crop. Previous studies have highlighted the benefits of potassium nitrate for cotton crops under controlled conditions at research centers. However, these results have yet to be validated in farmers' fields irrigated by the Western Canal. Productivity of cotton at farmers’ field is low as compare to its potential because of shortage of irrigation water is common in canal irrigated area. In first treatment foliar application of potassium nitrate @ 2% at flower initiation and ball formation stage with recommended dose of fertilizer however in second treatment there was no use of potassium nitrate with recommended dose of fertilizer. The results revealed that the seed cotton yield and lint percent were improved with two foliar application of potassium nitrate @ 2% at flower initiation and ball formation stage. Two foliar application of potassium nitrate @ 2% at flower initiation and ball formation stage increased partial factor productivity of applied nutrient, water use efficiency and water economic productivity as compared to control. Higher net realization and B:C ratio were obtained with foliar application of potassium nitrate @ 2% at flower initiation and ball formation stages as compare to control. Therefore, it is suggested that foliar application of potassium nitrate can be helpful to increase cotton yield, resource use efficiency and higher returns in farmers’ fields of canal irrigated area of ​​western India.